On-surface preparation of coordinated lanthanide-transition-metal clusters - Liu, Jing (Nat Commun, 2021)
The study of lanthanide (Ln)-transition-metal (TM) heterometallic clusters which play key roles in various high-tech applications is a rapid growing field of research. Despite the achievement of numerous Ln-TM cluster compounds comprising one Ln atom, the synthesis of Ln-TM clusters containing multiple Ln atoms remains challenging. Here, we present the preparation and self-assembly of a series of Au-bridged heterometallic clusters containing multiple cerium (Ce) atoms via on-surface coordination. By employing different pyridine and nitrile ligands, the ordered coordination assemblies of clusters containing 2, 3 and 4 Ce atoms bridged by Au adatoms are achieved on Au(111) and Au(100), as revealed by scanning tunneling microscopy. Density functional theory calculations uncover the indispensable role of the bridging Au adatoms in constructing the multi-Ce-containing clusters by connecting the Ce atoms via unsupported Ce-Au bonds. These findings demonstrate on-surface coordination as an efficient strategy for preparation and organization of the multi-Ln-containing heterometallic clusters.